The Analysis Go-Food of Sales (Case Study Salad Buah Kembar) - Mica Siar Meiriza; Ananda Sakinah; Jemelly Prisya Simanjuntak; Tiara Amanda; Yendita Pakpahan (Penerbit Jurnal Indonesia, 2025)
Salad Buah Kembar is a small and medium enterprise (MSME) food product with great potential to be developed in the market and in Go-food. However, sales of Salad Buah Kembar are still not optimal due to the lack of an effective marketing strategy. This research aims to develop a marketing strategy that can increase sales of Salad Buah Kembar in small and medium businesses. The research method used is a qualitative method with data collection techniques through interviews, observations, and document analysis. The results of the study show that an effective marketing strategy to increase sales of Salad Buah Kembar is to use the go food app, and develop innovative and high-quality products. In addition, this study also found that the factors that affect the sales of Salad Buah Kembar are product quality, price, and promotion. This research is expected to contribute to the development of effective marketing strategies to increase sales of Salad Buah Kembar in Small and Medium Enterprises (MSMEs).